A contribution to the control of voltage and power of the interconnection between two decentralized electrical grids with an optimal localization of the SVC devices in real-time - Ali Abderrazak Tadjeddine; A. Chaker; M. Khiat; L. Abdelmalek; N. Khalfalah (Institute of Advanced Engineering and Science, 2019)
Several problems related to the power grid in the region of Adrar, in southern Algeria, where it is not connected to the Algerian national network. This region contains many energy resources for power stations, wind and photovoltaic farms. The industrial development in this region requires a connection with the national network to rationalize renewable energy sources and allow sufficient capacity of power for the two grids. The work involved in studying the possibility of interconnection between the grid of Adrar region and the Algerian national network. Modeling, control and real-time analysis of various scenarios have been achieved. A SVC with an optimal location has controlled the improvement of the voltage of the interconnected grid.